Question

solve equation exp(3-n) = exp(2n)

242

likes1212 views

Velda

4.5

64 Answers

exp(3-n) = exp(2n)
3-n = 2n
3 = 2n+n
3 = 3n
n=3/3
n=1

Frequently asked questions (FAQs)

What is the probability of drawing two red cards in a standard deck of 52 playing cards without replacement?

+

Math question: What is the limit as x approaches infinity of (3x^2 - 2x + 5)/(4x^2 - x + 3)?

+

Math question: Find the value of sin(45°) + cos(30°) - tan(60°) using trigonometric ratio formulas.

+

New questions in Mathematics